Teaching Environmental Justice Teaching Environmental Justice Practices to Engage Students and Build Community - Jinnah, Sikina; Dubreuil, Jessie; Greene, Jody; S. Foster, Samara (Edward Elgar Publishing, 2023)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. This ground-breaking book explores ways to integrate environmental justice modules into courses across a wide variety of disciplines. Recommending accessible, flexible, and evidence-based pedagogical approaches designed by a multidisciplinary team of scholars, it centers equity and justice in student learning and course design and presents a model for faculty development that can be communicated across disciplines.